Loss-of-function variant in MAGT1 leading to XMEN disease in a Colombian patient with a common variable immunodeficiency - Sebastián Gutiérrez-Hincapié; Julio César Orrego; José Luis Franco; Claudia M. Trujillo-Vargas (Biomédica: revista del Instituto Nacional de Salud)
Introduction. Common variable immunodeficiency is a diagnosis of exclusion in immunodeficient patients with increased susceptibility to infections, hypogammaglobulinemia, deficient response to vaccination, or low percentages of switched memory B cells. In low- and middle-income countries, the elucidation and study of molecular defects in these patients may take decades. Objective. To elucidate the genetic defect conferring impaired immunity in a patient diagnosed with common variable immunodeficiency. Materials and methods. The clinical phenotype was extracted from the clinical records. NKG2D expression in natural killer cells was evaluated by flow cytometry. The whole exome sequencing was performed in the patient and his parents. Sanger sequencing confirmed the pathogenic variant. Results. The patient suffered from upper respiratory and urinary tract infections, autoimmune hemolytic anemia, and hepatopathy. NKG2D was decreased in the different blood subpopulations of natural killer cells. Serologic and viral load studies for Epstein-Barr virus were positive, but no B-cell malignancies have been documented. The patient presented a nonsense variant in the exon 3 of the MAGT1 gen (c.409C>T, rs387906724) in the X chromosome, resulting in an amino acid substitution of arginine for a stop codon in the position 137 of the protein (R137X). The mother also carried the pathogenic variant in a heterozygous state. Conclusions. We report the clinical case of the first Colombian male patient with a pathogenic variant in MAGT1 associated with XMEN disease. Genetic counseling and followup are recommended for families with similar cases to allow prompt detection of new cases.